A comprehensive study of the epidemiology of haematological malignancies in North Queensland. Issue 4 (15th August 2022) - Nath, Karthik; Boles, Rachael; Emeto, Theophilus I.; Adegboye, Oyelola A.; Castellanos, Maria Eugenia; Alele, Faith O.; Pearce, Jessica; Ewart, Barbara; Ward, Kayla; Lai, Hock C.; Morris, Edward; Hodges, Georgina; et al.
Abstract: Background: There is an absence of clinically relevant epidemiological data in regional Australia pertaining to haematological malignancies. Aim: To determine the incidence and geographical variation of haematological malignancies in North Queensland using a clinically appropriate disease classification. Methods: Retrospective, observational study of individual patient data records of all adults diagnosed with a haematological malignancy between 2005 and 2014 and residing within The Townsville Hospital Haematology catchment region. We report descriptive summaries, incidence rates and incidence‐rate ratios of haematological malignancies by geographic regions. Results: One thousand, five hundred and eighty‐one haematological malignancies (69% lymphoid, 31% myeloid) were diagnosed over the 10‐year study period. Descriptive data are presented for 58 major subtypes, as per the WHO diagnostic classification of tumours of haemopoietic and lymphoid tissues. The overall median age at diagnosis was 66 years with a male predominance (60%). We demonstrate a temporal increase in the incidence of haematological malignancies over the study period. We observed geographical variations in the age‐standardised incidence rates per 100 000 ranging from 0.5 to 233.5. Our data suggest an increased incidence rate ratio for haematological malignancies in some postcodes within the Mackay area compared with other regions. Conclusion: The present study successfully reports on the incidence of haematological malignancies in regional Queensland using a clinically meaningful diagnostic classification system and identifies potential geographic hotspots. We advocate for such contemporary, comprehensive and clinically meaningful epidemiological data reporting of blood cancer diagnoses in wider Australia. Such an approach will have significant implications towards developing appropriate data‐driven management strategies and public health responses for haematological malignancies.